2016
DOI: 10.4103/0971-9784.185526
|View full text |Cite
|
Sign up to set email alerts
|

Short-term prognostic value of perioperative coronary sinus-derived-serum cardiac troponin-I, creatine kinase-MB, lactate, pyruvate, and lactate-pyruvate ratio in adult patients undergoing open heart surgery

Abstract: Objectives:To investigate the release pattern of different cardiac metabolites and biomarkers directly from the coronary sinus (CS) and to establish the diagnostic discrimination limits of each marker protein and metabolites to evaluate perioperative myocardial injury in patients undergoing cardiac surgery under cardiopulmonary bypass (CPB).Patients and Methods:Sixty-eight patients undergoing first mitral and/or aortic valve replacements with/without coronary artery bypass grafting and Bentall procedure under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…During cardiac surgery, lactate is measured from the coronary sinus after reperfusion of the heart over time, Chowdhury, et al reported that lactate increased as myocardial damage strengthened. 15) This suggests that lactate accumulates in the heart as a result of the slow progression of myocardial injury, despite being stored in cooled cardiac preservation solution. Lactate then flows throughout the body after reperfusion, and HL is observed in arterial blood.…”
Section: Discussionmentioning
confidence: 99%
“…During cardiac surgery, lactate is measured from the coronary sinus after reperfusion of the heart over time, Chowdhury, et al reported that lactate increased as myocardial damage strengthened. 15) This suggests that lactate accumulates in the heart as a result of the slow progression of myocardial injury, despite being stored in cooled cardiac preservation solution. Lactate then flows throughout the body after reperfusion, and HL is observed in arterial blood.…”
Section: Discussionmentioning
confidence: 99%
“…Close hemodynamic, clinical, and biomarker-based monitoring continued from the perioperative to the intensive care setting provides early mobilization in a safe manner postcardiac surgery. [ 26 27 28 ]…”
Section: Discussionmentioning
confidence: 99%
“…These metabolic waste products are produced through glycolysis and provide indicators for anaerobic cell metabolism. The lactate/pyruvate ratio (L/P) has previously been used as an indicator for several ischemic-related medical conditions including acute liver failure [11], myocardial injury [12], and traumatic brain injury [13]. Soetens et al most recently demonstrated the use of these non-invasive inflammatory biomarkers as a potential indicator of pressure-induced tissue damage using the analytical assay described in this paper to detect and quantify levels of lactate and pyruvate collected from sweat and sebum samples [14].…”
Section: Introductionmentioning
confidence: 99%